1995
DOI: 10.1073/pnas.92.19.8856
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal long-term potentiation is impaired in mice lacking brain-derived neurotrophic factor.

Abstract: Brain-derived neurotrophic factor (BDNF), a member of the nerve growth factor (NGF) gene family, has been shown to influence the survival and differentiation of specific classes of neurons in vitro and in vivo. The possibility that neurotrophins are also involved in processes of neuronal plasticity has only recently begun to receive attention. To determine whether BDNF has a function in processes such as long-term potentiation (LTP), we produced a strain of mice with a deletion in the coding sequence of the BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
918
3
14

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,320 publications
(966 citation statements)
references
References 31 publications
31
918
3
14
Order By: Relevance
“…Consistent with these findings, BDNF enhances glutamatergic transmission at mature hippocampal synapses, in part by increases in presynaptic glutamate release (Kang and Schuman, 1996;Carmignoto et al, 1997;Li et al, 1998). At hippocampal and cortical synapses in vivo and in vitro, BDNF facilitates long-term potentiation, attenuates long-term depression and promotes homeostatic and competitive interactions that refine neural circuitry (Korte et al, 1995;Akaneya et al, 1996;Cabelli et al, 1996;Huang et al, 1999;Turrigiano and Nelson, 2000;Turrigiano and Nelson, 2004). At hippocampal and cerebellar synapses in BDNF-deficient mice, high-frequency stimulation and paired-pulse facilitation are impaired, which is consistent with compromised presynaptic release (Pozzo-Miller et al, 1999;Carter and Regehr, 2002).…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fsupporting
confidence: 54%
“…Consistent with these findings, BDNF enhances glutamatergic transmission at mature hippocampal synapses, in part by increases in presynaptic glutamate release (Kang and Schuman, 1996;Carmignoto et al, 1997;Li et al, 1998). At hippocampal and cortical synapses in vivo and in vitro, BDNF facilitates long-term potentiation, attenuates long-term depression and promotes homeostatic and competitive interactions that refine neural circuitry (Korte et al, 1995;Akaneya et al, 1996;Cabelli et al, 1996;Huang et al, 1999;Turrigiano and Nelson, 2000;Turrigiano and Nelson, 2004). At hippocampal and cerebellar synapses in BDNF-deficient mice, high-frequency stimulation and paired-pulse facilitation are impaired, which is consistent with compromised presynaptic release (Pozzo-Miller et al, 1999;Carter and Regehr, 2002).…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fsupporting
confidence: 54%
“…Numerous studies suggest that neurotrophic factors play important roles in brain plasticity. Neurotrophic factors can enhance neuronal sprouting (11), synaptogenesis (18), long-term potentiation (2,30,41), and neurotransmission (25) and increase neurotransmitter release (26,27,34). Humpel et al reported that human fetal cortical grafts expressed nerve growth factor, brain-derived neurotrophic factor, and neurotrophin-3 mRNA after transplantation to cortical cavities in rats (23).…”
Section: Discussionmentioning
confidence: 99%
“…Because long-term administration of moclobemide suppresses HPA activity and activates cAMP-mediated CREB phosphorylation via PKA, the expression of BDNF may be enhanced and followed by a profound alteration in synaptic efficiency (Korte et al 1995(Korte et al , 1996Chen et al 1999;Kafitz et al 1999). Furthermore, in these transgenic mice, morphine-induced mesolimbic release of serotonin and dopamine as well as the psychomotor-stimulant effects of morphine were enhanced.…”
Section: Consequences For Future Drug Treatment Of Depression Currentmentioning
confidence: 99%